İdare hukukunda kamu gücü kavramı - Cabıoğlu, Saniye Sena (My University, 2017)
ÖZETKamu gücü, idarenin kamu yararını gerçekleştirmek amacıyla hizmetlerini yürütürken sahip olduğu ayrıcalıklar olup kavram, idare hukukunun görev ve faaliyet alanını belirleyen önemli, hatta anahtar bir kavram olmuştur. Bu noktada tezde kamu gücü kavramının gelişimi, doğuşu ve teorileri ele alınarak kavramın idari işlemlerde ve faaliyetlerde nasıl ortaya çıktığı belirlenmiştir. Bu kapsamda özellikle tek taraflılık kavramı üzerinde durulmuştur. Benzer şekilde kamu gücünün idari sözleşmelerde üstün yetkilerinin nasıl ortaya çıktığı ifade edilmiştir. (Tek taraflı olarak sözleşmenin şartlarını düzenleme, denetleme, ifa, yaptırım, tek taraflı değişiklik yapma yetkilerinde olduğu gibi)

THE CONCEPT OF PUBLIC POWER IN ADMINISTRATIVE LAWThe public power is the privilege that the administration has in carrying out its services in order to realize the public interest, and the concept has become an important, even key concept that determines the duty and activity field of administrative law. At this point, the development of the concept of public power in the thesis, the birth and the theories of the concept was taken into account and how it emerged in administrative processes and activities. In this context, especially the concept of unilateralism is emphasized. In a similar vein, it has been expressed how superior powers emerge in administrative contracts of public power. (Such as unilaterally having the authority to regulate, supervise, execute, sanction, unilaterally change the conditions of the contract)
Keywords: İdare hukuku; KAMU GÜCÜ PUBLIC POWER; Kamu hukuku; Türkiye